The Corporate Secretary : The Governance Professional - International Finance Corporation (International Finance Corporation, Washington, DC, 2016)
This Handbook offers a concise and practical description of how corporate secretaries might carry out their role to improve governance in their organizations. It can also serve as a guidance tool for both International Finance Corporation (IFC) clients and advisory staff to clarify the potentially expansive duties of corporate secretaries and to help them assist corporate secretaries in understanding what skills they require to fulfill their roles. The Handbook is based on IFC’s publication, Corporate Secretaries Toolkit, which provides a portfolio of modules that cover topics of interest and value to those carrying out the role of corporate secretary and to the companies and organizations they serve. It also provides trainers with materials and instructions for conducting training.